Analysis of The Effect of Servicescape and Service Quality on Customer Satisfaction at Post Shop Coffee Tofee in Bogor City - Yunita, Riani; Shihab, Muchsin S.; Jonas, Dendy; Haryani, Hendriyati; Anggraini Terah , Yochebed (Pandawan, 2022)
This study aims to determine how servicescape and service quality affect customer satisfaction and word of mouth. This research is based on customer satisfaction as a benchmark for business continuity that can have an impact on marketing, with pre-survey results based on visitor testimonials from 20 people interviewed, as many as 55% of consumers are dissatisfied with servicescape and as many as 45% of consumers are dissatisfied with quality. service and only as much as 40% whose satisfaction affects word of mouth. This research was conducted at Post Shop Coffee Toffee Bogor City, with a total of 100 respondents with two equations, namely equation I Y1 = PY1X1 + PY1X2 + ?1 and equation II: Y2 = PY2X1 + PY2X2 + PY2Y1 + ?2. The analysis used in this research begins with the classic assumption test in the form of normality test and heteroskesdasticity test, path analysis with t test; f test; and codetermination test and coefficient test between variables. The results showed that the normality test for equation I and equation II, the value of sig. > 0.05 means that the data residuals are normally distributed. Equations I and II do not occur heteroskesdasticity, that is, they are not patterned regularly and spread above and below the number 0. The T test for equation I obtained a calculated T value of 3.885 and 5,279 greater than T table 1985, the sig value of 0.000 less than 0.05 means that H0 is rejected and H1 is accepted, it means that both servicescape and service quality have an influence on customer satisfaction. The F test for the servicescape variable and service quality obtained the calculated F value of 88,319, greater than the F table of 3.090 and the sig 0,000 value smaller than 0.05, meaning that H0 is rejected and H1 is accepted. The contribution of the influence of X1 servicescape and X2 service quality on Y1 customer satisfaction amounted to 64.6%. T test for equation II, it is obtained that the value of T count is greater than T table 1.985, the sig value of 0.000 is less than 0.05, which means that service quality and customer satisfaction have an influence on word of mouth on consumers of Post Shop Coffee Tofee in Bogor City. The F test for the servicescape variable, service quality and customer satisfaction obtained a calculated F value of 129,419 greater than the F table of 2,699 and a sig 0,000 value less than 0.05, meaning that there is a joint influence between servicescape, service quality and customer satisfaction on word of mouth. The contribution or contribution of the influence of servicescape (X1), service quality (X2) and customer satisfaction (Y1) to word of mouth (Y2) is 80.2%. The correlation between customer satisfaction and word of mouth is 0.874 which means that customer satisfaction has a strong relationship. very strong against word of mouth.